THE POWER OF BODY LANGUAGE IN EFFECTIVE COMMUNICATION - Qarshiyeva Barchin Abdimurodovna; Karshiyeva Gulsinaxon Toʻlqin qizi; Jumayeva Durdona Malikovna (TADQIQOTLAR, 2025)
Abstract Body  language,  encompassing  gestures,  facial  expressions,  posture,  and  eye contact, is a critical component of human communication, often conveying more than verbal  language.  This  article  explores  the  power  of  body  language  in  shaping interpersonal interactions, with a focus on its applications in professional, social, and cross-cultural contexts. Through comparative analysis of body language practices in the  United  States,  China,  Brazil,  and  Uzbekistan,  we  examine  how  cultural  norms influence nonverbal communication and its interpretation. The findings highlight the importance of understanding body language to enhance communication effectiveness, build  trust,  and  avoid  misunderstandings.  This  study  offers  practical  strategies  for leveraging  body  language  in  diverse  settings,  contributing  to  communication scholarship and intercultural competence.